Determination and comparison of rainwater quality at Kuala Pilah and Seremban, Negeri Sembilan based on topography / Nur Nasyrah Noorazam - Noorazam, Nur Nasyrah (Faculty of Applied Sciences, 2017)
Water is the basic of life. Rainwater are one of the water resources. The quality of rainwater had been study in Kuala Pilah and Seremban based on topography. Kuala Pilah acts as a rural area while Seremban acts as an urban area. Physicochemical analysis was done to determine the pH, temperature, conductivity, resistivity and TDS. The chemical analysis by using FAAS method to determine the concentration of an ion that present in the samples. Microbial analysis is also test on the samples to calculate the CFU. The results are compared to differentiate the rainwater quality. The samples of Seremban were slightly containing more acidic rainwater than Kuala Pilah sample. Seremban samples also show high value in temperature, conductivity and TDS except for resistivity. Seremban samples had high concentration of Copper and Magnesium ion while Kuala Pilah sample had high concentration in Iron ion. Samples of Seremban show higher number of CFU number compare to sample of Kuala Pilah. The t-test analysis was done to support the result and show 89% of the significant value is greater than 0.05. This might show the variablitity in both condition are about the equal. Based on the statistic value might conclude that there is a 78% statistically significant difference between rainwater at Kuala Pilah and Seremban. This shows that the condition of topographic of the study area is affecting the rainwater quality.